Pengaruh Modal Sosial terhadap Keberhasilan Program Pemberdayaan Masyarakat: Studi Empiris di Desa Mantar, Kabupaten Sumbawa Barat - Pratama, Ahmad Fadli; Mahendra Saputra, Rizky (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
This study aims to analyze the effect of social capital on the success of community empowerment programs in Mantar Village, West Sumbawa Regency. Social capital is understood as a social resource consisting of trust, social networks, and social norms embedded in the community. The study applies a quantitative approach using an explanatory survey design. Data were collected through questionnaires distributed to community members directly involved in empowerment programs. Data analysis employed descriptive statistics and simple linear regression. The findings indicate that the level of social capital in Mantar Village is relatively high. Trust and social networks are the most influential dimensions in encouraging community participation. Regression analysis results show that social capital has a positive and significant effect on the success of community empowerment programs. Program success is mainly reflected in high levels of community participation and program sustainability, although economic impacts are not yet evenly distributed. The study concludes that strengthening social capital is a key factor in enhancing the effectiveness of community empowerment programs. These findings highlight the importance of incorporating social dimensions into the planning and implementation of sustainable village development policies.